PAC1 receptor blockade reduces central nociceptive activity: new approach for primary headache?. Issue 7 (July 2020) - Hoffmann, Jan; Miller, Silke; Martins-Oliveira, Margarida; Akerman, Simon; Supronsinchai, Weera; Sun, Hong; Shi, Licheng; Wang, Judy; Zhu, Dawn; Lehto, Sonya; Liu, Hantao; Yin, Ruoyuan; et al.
Abstract : Abstract: Pituitary adenylate cyclase activating polypeptide-38 (PACAP38) may play an important role in primary headaches. Preclinical evidence suggests that PACAP38 modulates trigeminal nociceptive activity mainly through PAC1 receptors while clinical studies report that plasma concentrations of PACAP38 are elevated in spontaneous attacks of cluster headache and migraine and normalize after treatment with sumatriptan. Intravenous infusion of PACAP38 induces migraine-like attacks in migraineurs and cluster-like attacks in cluster headache patients. A rodent-specific PAC1 receptor antibody Ab181 was developed, and its effect on nociceptive neuronal activity in the trigeminocervical complex was investigated in vivo in an electrophysiological model relevant to primary headaches. Ab181 is potent and selective at the rat PAC1 receptor and provides near-maximum target coverage at 10 mg/kg for more than 48 hours. Without affecting spontaneous neuronal activity, Ab181 effectively inhibits stimulus-evoked activity in the trigeminocervical complex. Immunohistochemical analysis revealed its binding in the trigeminal ganglion and sphenopalatine ganglion but not within the central nervous system suggesting a peripheral site of action. The pharmacological approach using a specific PAC1 receptor antibody could provide a novel mechanism with a potential clinical efficacy in the treatment of primary headaches. Abstract : PAC1 receptor blockade using a monoclonal antibody inhibits nociceptive neuronal activity in the trigeminocervical complex.